2002
DOI: 10.1111/1468-2508.00127
|View full text |Cite
|
Sign up to set email alerts
|

Campaign Advertising: Partisan Convergence or Divergence?

Abstract: Prior research demonstrates that many citizens are unable to perceive differences between the two major political parties. In order to investigate whether candidate behavior in campaigns contributes to this perception, we test implications about partisan constraints on campaign rhetoric drawn from the literature on parties and policy convergence. Our results suggest that candidates of different parties do not highlight the same issues or positions in their campaign advertising. We find that campaign rhetoric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
69
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 11 publications
3
69
0
Order By: Relevance
“…While some research shows that parties indeed fail to address the same topics in campaigns Farlie 1983, Spiliotes andVavreck 2002), other studies have found that parties in fact do engage with each other (Sigelman and Buell 2004, Damore 2005, Green-Pedersen 2007, Dolezal et al 2014. In any case, it is not possible to say that party competition in general is driven either by engagement or avoidance as issue engagement will vary across parties and by issue area (Green-Pedersen and Mortensen forthcoming; Kaplan et al 2006;Wagner and Meyer 2014).…”
Section: Issue Engagement In a Multiparty Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…While some research shows that parties indeed fail to address the same topics in campaigns Farlie 1983, Spiliotes andVavreck 2002), other studies have found that parties in fact do engage with each other (Sigelman and Buell 2004, Damore 2005, Green-Pedersen 2007, Dolezal et al 2014. In any case, it is not possible to say that party competition in general is driven either by engagement or avoidance as issue engagement will vary across parties and by issue area (Green-Pedersen and Mortensen forthcoming; Kaplan et al 2006;Wagner and Meyer 2014).…”
Section: Issue Engagement In a Multiparty Contextmentioning
confidence: 99%
“…While most comparable studies of press releases are based on policy areas (e.g. Brandenburg 2002, Hopmann et al 2012, Spiliotes and Vavreck 2002, Sigelman and Buell 2004, Tedesco 2005a, 2005b, we measure engagement at the level of individual issues. 1 Measures based on policy areas may identify high levels of issue engagement even when parties address issues that are completely unrelated to each other (see also Lipsitz 2013).…”
Section: Measuring Issue Engagement In Party Press Releasesmentioning
confidence: 99%
“…While some studies show that issue ownership influences what political parties talk about (e.g. Budge and Farlie 1983;Petrocik 1996;Petrocik et al 2003;Spiliotes and Vavreck 2002), others demonstrate that parties respond to the policy priorities of their voters (e.g. Klüver and Spoon 2014;Spoon and Klüver 2014;Wagner and Meyer 2014).…”
mentioning
confidence: 99%
“…In addition, the vast majority of studies investigating selective issue emphasis of political parties focuses on political communication in the United States (e.g. Damore 2005;Petrocik 1996;Sides 2007;Sigelman and Buell 2004;Spiliotes and Vavreck 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation